In vitro assessment of antibacterial and biocompatibility properties of a poly-ε-lysine and hyaluronic acid contact-killing coating to prevent prosthetic joint infection - Julia L. van Agtmaal; Anniek M.C. Gielen; Sanne W.G. van Hoogstraten; Laura C.W. Peeters; Aghilas Akkache; Rajendra Kasinath; Nihal Engin Vrana; Nick R.M. Beijer; Tim J.M. Welting; Cynthia Calligaro; Jacobus J.C. Arts (PLoS ONE, 2026)
Prosthetic joint infection (PJI) is a major adverse outcome following total hip and knee arthroplasties. With the rise of antimicrobial resistance, there is a risk of therapeutic insufficiency in treating PJI. This study determined the potential of a poly-ε-lysine and hyaluronic acid (PEL-10/HA144-1) contact-killing coating as a promising prevention of bacterial attachment. A broader development perspective was integrated through a Safe-by-Design approach by adding relevant in vitro tests for implant-host interactions. The PEL-10/HA144-1 coating was deposited on titanium alloy Ti6Al4V (Ti) and ultra-high-molecular-weight-polyethylene (UHMWPE). A combination of the ISO 22196, ASTM E2180-18, and JIS Z 2801 testing standards using Staphylococcus aureus and Escherichia coli demonstrated a bactericidal effect of the coating, up to a 5-log reduction compared to uncoated samples. A bacterial adhesion test showed a decrease in adherent bacteria up to 4-log after 4 h, and up to 5-log after 24 h between coated and uncoated samples. Saos-2 human osteoblast-like cells and L929 mouse fibroblasts exposed to 72 h extracts of the coating for 24 h showed in vitro cell viability of >70%, indicating no cytotoxicity according to ISO 10993−5. Furthermore, while initial osteoblast attachment to the coating appeared challenging, increased proliferation and metabolic activity over time were observed. After 14 and 21 days, no reduction in osteogenic marker expression was found on the coated samples compared to the uncoated samples. Overall, the PEL-10/HA144-1 coating reduced bacterial adhesion, was not cytotoxic to mammalian cells , and supported osteoblast function in vitro , making it a promising technique for future implantable orthopedic applications.